Diversely substituted quinolines via rhodium-catalyzed alkyne hydroacylation - Willis, M; Neuhaus, J; Brunavs, M; Morrow, S (American Chemical Society, 2016)
The Rh-catalyzed hydroacylative union of aldehydes and o-alkynyl anilines leads to 2-aminophenyl enones, and onwards to substituted quinolines. The mild reaction conditions employed in this chemistry result in a process that displays broad functional group tolerance allowing the preparation of diversely substituted quinolines in high yields. Extension to the use of o-alkynyl nitro arenes as substrates, leads to 2-nitrochalcones, from which both quinolines and quinoline N-oxides can be accessed.>